Glass composition for glass fibers, glass fibers, glass fiber fabric, and glass fiber-reinforced resin composition

By using a glass composition for glass fibers of specific composition, the problem of the strength of glass long fibers in water, high temperature and humidity environments is solved, and the high strength and long fiberization of glass filaments in harsh environments is achieved.

CN119923375AActive Publication Date: 2025-05-02NITTO BOSEKI CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202480003762.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-31
Filing Date
2024-06-05
Publication Date
2025-05-02
Estimated Expiration
2044-06-05

AI Technical Summary

Technical Problem

Long glass fibers can easily lead to strength reduction, product deterioration and fiber breakage in water, high temperature and humidity environments, causing problems of tiny fluff.

Method used

A glass composition for glass fibers with a specific composition is used, which contains components such as SiO2, Al2O3, B2O3, MgO and CaO. The total content of MgO and CaO is in the range of 17.09 to 30.00 mass %, and the MgO/CaO ratio is between 0.29 and 1.92 to improve the biological solubility and long fibrosis ability of glass filaments.

Benefits of technology

The glass filaments are maintained at sufficiently high strength in water, high temperature and humid environments, and the strength decrease and product deterioration are avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005281031610000271
    Figure BDA0005281031610000271
Patent Text Reader

Abstract

Provided is a glass composition for glass fibers, which has biosolubility, can achieve long fibration, and can obtain a glass filament having sufficiently high strength even when exposed to water, high-temperature and humid environments. This glass composition for glass fibers contains, relative to the total amount, 35.00 to 50.00 mass% of SiO2, 12.00 to 28.00 mass% of Al2O3, 10.00 to 25.00 mass% of B2O3, 2.00 to 18.00 mass% of MgO, and 5.00 to 25.00 mass% of CaO, the total content of MgO and CaO being 17.09 to 30.00 mass%, and MgO / CaO being 0.29 to 1.92.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a glass composition for glass fiber, glass fiber, glass fiber fabric and a glass fiber reinforced resin composition. Background Art

[0002] In recent years, glass fiber reinforced resin compositions, especially printed wiring boards containing glass fiber fabrics, have been continuously being made thinner and smaller, and correspondingly, glass long fibers are required to be extremely fine. Therefore, it is expected that biosolubility will also become an important property in the field of glass long fibers in the future.

[0003] Therefore, the present inventors have proposed a glass composition for glass fibers that has biosolubility and can be formed into long fibers (see Patent Document 1).

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent No. 7107468 Summary of the invention

[0007] Problems to be solved by the invention

[0008] The long glass fibers are exposed to water in the process of applying a surface treatment agent to the surface of the glass fibers during the spinning process, in the process of opening the glass fiber fabric during the process of processing the glass fibers into glass yarn bundles, glass yarns, glass fiber fabrics, etc. In addition, when the long glass fibers are processed into final products such as glass fiber reinforced resin compositions and when they are used as final products, if they are stored for a long time in a warehouse with insufficient air conditioning management, they may be exposed to a high temperature and high humidity environment depending on the meteorological conditions.

[0009] However, biosoluble long glass fibers are hydrophilic and therefore have low water resistance. If exposed to water or a high temperature and high humidity environment, the strength of the glass filaments decreases, product degradation accelerates, or the glass filaments break due to tension applied during transportation, which is the main cause of the formation of fine fluff.

[0010] Therefore, the object of the present invention is to eliminate the above-mentioned problems and provide a glass composition for glass fiber that has biosolubility, can be formed into long fibers, and can obtain glass filaments with sufficiently high strength even when exposed to water or in a high-temperature and high-humidity environment.

[0011] Means for solving problems

[0012] In order to achieve the above-mentioned purpose, the glass composition for glass fiber of the present invention is characterized in that it contains SiO2 in a range of 35.00 to 50.00 mass%, Al2O3 in a range of 12.00 to 28.00 mass%, B2O3 in a range of 10.00 to 25.00 mass%, MgO in a range of 2.00 to 18.00 mass% and CaO in a range of 5.00 to 25.00 mass%, relative to the total amount, the total content of MgO and CaO is in the range of 17.09 to 30.00 mass%, and the ratio of the content of MgO to the content of CaO (MgO / CaO) is in the range of 0.29 to 1.92.

[0013] With the above-mentioned structure, the glass composition for glass fibers of the present invention can provide glass filaments which have biosolubility, can be elongated, and have sufficiently high strength even when exposed to water or a high-temperature, high-humidity environment.

[0014] Among them, having biosolubility means that the biosolubility described later is 100 μg / h or more; being able to achieve long fiberization means that the operating temperature range, which is the difference between 1000 poise temperature and liquidus temperature, is above 0°C; having sufficiently high strength even when exposed to water or in a high temperature and humid environment means that the strength upon water absorption described later is 2.1 GPa or more (i.e., having a strength upon water absorption that is equal to or higher than that of glass fibers composed of E glass).

[0015] In the glass composition for glass fiber of the present invention, the ratio of the MgO content to the CaO content (MgO / CaO) is preferably in the range of 0.49 to 1.68, so that glass filaments can be obtained that are biosoluble, easy to be elongated, and have excellent strength even when exposed to water or a high temperature and high humidity environment.

[0016] Among them, easy to achieve long fiber means that the difference between 1000 poise temperature and liquid phase temperature, that is, the operating temperature range is above 100°C; excellent strength even when exposed to water or high temperature and humidity environment means that the strength when absorbing water described later is above 2.3 GPa.

[0017] The glass fiber of the present invention is characterized by comprising glass filaments formed from the glass composition for glass fibers of the present invention. In the glass fiber of the present invention, preferably, the glass filaments have a filament diameter of less than 3.0 μm.

[0018] Furthermore, the glass fiber fabric and the glass fiber-reinforced resin composition of the present invention are characterized by comprising the glass fiber of the present invention. DETAILED DESCRIPTION

[0019] Next, embodiments of the present invention will be described in further detail.

[0020] The glass composition for glass fiber of the present embodiment contains SiO2 in the range of 35.00 to 50.00 mass %, Al2O3 in the range of 12.00 to 28.00 mass %, B2O3 in the range of 10.00 to 25.00 mass %, MgO in the range of 2.00 to 18.00 mass % and CaO in the range of 5.00 to 25.00 mass %, relative to the total amount, the total content of MgO and CaO is in the range of 17.09 to 30.00 mass %, and the ratio of the content of MgO to the content of CaO (MgO / CaO) is in the range of 0.29 to 1.92.

[0021] In the glass composition for glass fiber of the present embodiment, if SiO2 is less than 35.00 mass % relative to the total amount, the strength and elastic modulus of the long glass fiber are reduced, and when the long glass fiber is used in a composite material with a resin, the effect of strengthening the resin becomes insufficient. On the other hand, when SiO2 exceeds 50.00 mass % relative to the total amount, it is possible to reduce biosolubility.

[0022] In the glass composition for glass fiber of the present embodiment, the content of SiO2 relative to the total amount is preferably in the range of 35.50 to 49.40 mass %, more preferably in the range of 37.00 to 48.90 mass %, further preferably in the range of 38.00 to 47.90 mass %, particularly preferably in the range of 39.00 to 47.00 mass %, particularly preferably in the range of 40.00 to 46.00 mass %, extremely preferably in the range of 41.00 to 45.00 mass %, and most preferably in the range of 41.60 to 44.40 mass %.

[0023] In addition, in the glass composition for glass fiber of the present embodiment, if Al2O3 is less than 12.00 mass % relative to the total amount, the strength and elastic modulus of the long glass fiber are reduced, and when used to manufacture a composite material thereof with a resin, the effect of reinforcing the resin becomes insufficient. On the other hand, when Al2O3 exceeds 28.00 mass % relative to the total amount, the devitrification temperature of the molten glass becomes high, and it may be difficult to implement long fiberization.

[0024] In the glass composition for glass fiber of the present embodiment, the content of Al2O3 relative to the total amount is preferably in the range of 15.10 to 27.00 mass %, more preferably in the range of 16.10 to 26.00 mass %, further preferably in the range of 17.00 to 25.00 mass %, particularly preferably in the range of 18.00 to 24.00 mass %, extremely preferably in the range of 18.50 to 23.00 mass %, and most preferably in the range of 19.00 to 22.00 mass %.

[0025] In addition, in the glass composition for glass fiber of the present embodiment, if B2O3 is less than 10.00 mass % relative to the total amount, the devitrification temperature of the molten glass becomes high, and it is possible to make it difficult to grow fibers, and the biosolubility is likely to decrease. On the other hand, if B2O3 exceeds 25.00 mass % relative to the total amount, the molten glass will undergo phase separation, and it is difficult to grow fibers.

[0026] In the glass composition for glass fiber of the present embodiment, the content of B2O3 relative to the total amount is preferably in the range of 11.10 to 24.00 mass %, more preferably in the range of 12.00 to 21.30 mass %, further preferably in the range of 12.30 to 18.00 mass %, particularly preferably in the range of 12.50 to 17.50 mass %, particularly preferably in the range of 12.70 to 17.00 mass %, extremely preferably in the range of 12.80 to 16.50 mass %, and most preferably in the range of 13.50 to 16.20 mass %.

[0027] In addition, in the glass composition for glass fiber of the present embodiment, if MgO is less than 2.00 mass % relative to the total amount, the elastic modulus of the long glass fiber decreases, and when the long glass fiber is used to make a composite material with a resin, the effect of reinforcing the resin becomes insufficient. On the other hand, if MgO exceeds 18.00 mass % relative to the total amount, the strength of the long glass fiber decreases, and when the long glass fiber is used to make a composite material with a resin, the effect of reinforcing the resin becomes insufficient.

[0028] In the glass composition for glass fiber of the present embodiment, the content of MgO relative to the total amount is preferably in the range of 3.10 to 17.00 mass %, more preferably in the range of 5.10 to 16.00 mass %, further preferably in the range of 6.10 to 15.40 mass %, particularly preferably in the range of 8.10 to 15.00 mass %, particularly preferably in the range of 8.40 to 14.00 mass %, extremely preferably in the range of 8.60 to 13.00 mass %, further extremely preferably in the range of 8.70 to 12.00 mass %, and most preferably in the range of 9.10 to 11.95 mass %.

[0029] In addition, in the glass composition for glass fiber of the present embodiment, if CaO is less than 5.00 mass % relative to the total amount, the elastic modulus of the long glass fiber is reduced, and when the long glass fiber is used to make a composite material with a resin, the effect of reinforcing the resin becomes insufficient. On the other hand, if CaO exceeds 25.00 mass % relative to the total amount, the strength of the long glass fiber is reduced, and when the long glass fiber is used to make a composite material with a resin, the effect of reinforcing the resin becomes insufficient.

[0030] In the glass composition for glass fiber of the present embodiment, the content of CaO relative to the total amount is preferably in the range of 5.60 to 24.00 mass %, more preferably in the range of 6.60 to 23.00 mass %, further preferably in the range of 10.10 to 22.50 mass %, particularly preferably in the range of 13.40 to 22.00 mass %, particularly preferably in the range of 13.80 to 21.90 mass %, and most preferably in the range of 14.00 to 17.90 mass %.

[0031] In addition, in the glass composition for glass fiber of the present embodiment, if the total content of MgO and CaO relative to the total amount is less than 17.09 mass %, the strength of the glass filaments when the glass long fibers absorb water decreases. On the other hand, if the total content of MgO and CaO relative to the total amount exceeds 30.00 mass %, the strength of the glass long fibers decreases, and when the glass long fibers are used to make a composite material with a resin, the effect of strengthening the resin becomes insufficient.

[0032] In the glass composition for glass fiber of the present embodiment, the total content of MgO and CaO relative to the total amount is preferably in the range of 18.00 to 29.00 mass %, more preferably in the range of 19.00 to 28.00 mass %, further preferably in the range of 20.00 to 27.00 mass %, particularly preferably in the range of 20.50 to 26.00 mass %, particularly preferably in the range of 21.00 to 25.00 mass %, and most preferably in the range of 22.00 to 24.50 mass %.

[0033] In addition, in the glass composition for glass fiber of the present embodiment, if the ratio of the content of MgO to the content of CaO (MgO / CaO) is less than 0.29, the strength of the glass filaments when the glass filaments absorb water decreases. On the other hand, if the ratio of the content of MgO to the content of CaO (MgO / CaO) exceeds 1.92, the devitrification temperature of the molten glass becomes high, and it becomes difficult to form long fibers.

[0034] In the glass composition for glass fiber of the present embodiment, the ratio of the MgO content to the CaO content (MgO / CaO) is preferably in the range of 0.34 to 1.75, more preferably in the range of 0.49 to 1.68, further preferably in the range of 0.51 to 1.30, particularly preferably in the range of 0.52 to 0.99, and most preferably in the range of 0.61 to 0.92.

[0035] In the glass composition for glass fiber of the present embodiment, the total content of SiO2, B2O3, Al2O3, CaO and MgO relative to the total amount is, for example, 91.00 mass % or more, preferably 95.00 mass % or more, more preferably 98.00 mass % or more, further preferably 99.00 mass % or more, particularly preferably 99.30 mass % or more, particularly preferably 99.50 mass % or more, extremely preferably 99.70 mass % or more, and most preferably 99.90 mass % or more.

[0036] From the viewpoint of improving the degassing property of molten glass and improving the stability of long fiber formation, the glass composition for glass fiber of the present embodiment may contain Fe2O3. The content of Fe2O3 is, for example, in the range of 0 to 0.40 mass %, preferably in the range of 0 to 0.30 mass %, more preferably in the range of 0 to 0.20 mass %, further preferably in the range of 0 to 0.10 mass %, particularly preferably in the range of 0 to 0.05 mass %, and most preferably in the range of 0 to 0.01 mass %.

[0037] In addition, from the viewpoint of reducing the melt viscosity of the molten glass and easily achieving long fibers, the glass composition for glass fibers of the present embodiment may contain ZrO2. The content of ZrO2 is, for example, in the range of 0 to 0.60 mass % relative to the total amount of the glass composition for glass fibers of the present embodiment, preferably in the range of 0 to 0.30 mass %, more preferably in the range of 0 to 0.20 mass %, further preferably in the range of 0 to 0.10 mass %, particularly preferably in the range of 0 to 0.05 mass %, and most preferably in the range of 0 to 0.01 mass %.

[0038] From the viewpoint of improving the defoaming property of molten glass and improving the stability of long fiberization, the glass composition for glass fiber of the present embodiment may contain F2 and Cl2. The total content of F2 and Cl2 relative to the total amount of the composition for glass fiber of the present embodiment is, for example, in the range of 0 to 0.40 mass %, preferably in the range of 0 to 0.30 mass %, more preferably in the range of 0 to 0.20 mass %, further preferably in the range of 0 to 0.10 mass %, particularly preferably in the range of 0 to 0.05 mass %, and most preferably in the range of 0 to 0.01 mass %.

[0039] From the viewpoint of reducing the melt viscosity of the molten glass and facilitating the formation of long fibers, the glass composition for glass fibers of the present embodiment may contain SrO. The content of SrO is, for example, in the range of 0 to 0.40 mass %, preferably in the range of 0 to 0.30 mass %, more preferably in the range of 0 to 0.20 mass %, further preferably in the range of 0 to 0.10 mass %, particularly preferably in the range of 0 to 0.05 mass %, and most preferably in the range of 0 to 0.01 mass %.

[0040] From the viewpoint of suppressing the rise of the devitrification temperature of the molten glass and making it easy to implement long fibers, the glass composition for glass fibers of the present embodiment may contain ZnO. The content of ZnO is, for example, in the range of 0 to 0.40 mass %, preferably in the range of 0 to 0.30 mass %, more preferably in the range of 0 to 0.20 mass %, further preferably in the range of 0 to 0.10 mass %, particularly preferably in the range of 0 to 0.05 mass %, and most preferably in the range of 0 to 0.01 mass %.

[0041] From the viewpoint of suppressing the rise of the devitrification temperature of the molten glass and facilitating the long fiberization, the glass composition for glass fiber of the present embodiment may contain SnO2. The content of SnO2 is, for example, in the range of 0 to 0.40 mass % relative to the total amount of the glass composition for glass fiber of the present embodiment, preferably in the range of 0 to 0.30 mass %, more preferably in the range of 0 to 0.20 mass %, further preferably in the range of 0 to 0.10 mass %, particularly preferably in the range of 0 to 0.05 mass %, and most preferably in the range of 0 to 0.01 mass %.

[0042] From the viewpoint of suppressing the increase of the devitrification temperature of the molten glass and facilitating the long fiberization, the glass composition for glass fiber of the present embodiment may contain P2O5. From the viewpoint of suppressing the generation of bubbles in the molten glass, the content of P2O5 is, for example, less than 2.50 mass % relative to the total amount of the glass composition for glass fiber of the present embodiment, preferably less than 1.50 mass %, more preferably less than 1.00 mass %, further preferably less than 0.80 mass %, extremely preferably less than 0.60 mass %, and most preferably less than 0.50 mass %.

[0043] In the case where the glass composition for glass fiber of the present embodiment includes TiO2, the content of TiO2 is, for example, in the range of 1.90 mass % or less relative to the total amount of the glass composition for glass fiber of the present embodiment, and is preferably in the range of 0 to 0.40 mass %, more preferably in the range of 0 to 0.20 mass %, further preferably in the range of 0 to less than 0.10 mass %, particularly preferably in the range of 0 to 0.05 mass %, and most preferably in the range of 0 to 0.01 mass %. If TiO2 exceeds 1.90 mass %, when the glass composition for glass fiber is made into glass fiber, the biosolubility may be reduced.

[0044] From the viewpoint of reducing the melt viscosity of the molten glass and easily achieving long fibers, the glass composition for glass fibers of the present embodiment may contain Li2O, K2O and Na2O. The total content of Li2O, K2O and Na2O is, for example, in the range of 0 to 0.90 mass %, preferably in the range of 0 to 0.40 mass %, more preferably in the range of 0 to 0.20 mass %, further preferably in the range of 0 to 0.10 mass %, particularly preferably in the range of 0 to 0.05 mass %, and most preferably in the range of 0 to 0.01 mass %.

[0045] The glass composition for glass fiber of the present embodiment may contain oxides of Ba, Mn, Co, Ni, Cu, Mo, W, Ce, Y, La, Bi, Gd, Pr, Sc or Yb as impurities in a total content of less than 1.00 mass % relative to the total amount of the glass composition for glass fiber, wherein the impurities are derived from the raw materials. In particular, when the glass composition for glass fiber of the present embodiment contains BaO, CeO, Y2O3, La2O3, Bi2O3, Gd2O3, Pr2O3, Sc2O3 or Yb2O3 as impurities, the content of each oxide is preferably less than 0.40 mass %, more preferably less than 0.20 mass %, further preferably less than 0.10 mass %, particularly preferably less than 0.05 mass %, extremely preferably less than 0.01 mass %, and most preferably less than 0.004 mass %.

[0046] In addition, when the glass composition for glass fiber of the present embodiment is made into glass fiber, from the viewpoint of having a more excellent elastic modulus, the ratio of the content of MgO to the content of Al2O3 (MgO / Al2O3) is preferably 0.28 or more, and from the viewpoint of excellent water resistance when made into glass fiber, it is preferably 0.63 or less. The ratio of the content of MgO to the content of Al2O3 (MgO / Al2O3) is preferably in the range of 0.28 to 0.77, and more preferably in the range of 0.41 to 0.63.

[0047] Moreover, when the glass composition for glass fiber of the present embodiment is made into glass fiber, from the viewpoint of having better biosolubility and easy fiberization, the content S of SiO2, the content A of Al2O3, the content B of B2O3, the content M of MgO, and the content C of CaO preferably satisfy the following formula (1), and more preferably satisfy the following formula (2).

[0048] 20.8≤S×(C+M) / (A+B)≤34.0…(1)

[0049] 27.0≤S×(C+M) / (A+B)≤33.0…(2)

[0050] In the above formula (1) or the above formula (2), as described above, if C+M is too small, there is a tendency that the strength of the glass filaments when the glass fiber absorbs water is reduced. On the other hand, if C+M is too large, the viscosity of the glass is reduced, and the operating temperature range is narrowed, so there is a tendency that it is difficult to achieve long fiberization. In addition, S / (A+B) represents the ratio of the content of SiO2 in the components forming the skeleton of the glass to the total content of Al2O3 and B2O3. If the ratio is too small, there is a tendency that the mechanical properties of the glass fiber are deteriorated. On the other hand, if the ratio is too large, there is a tendency that the meltability is deteriorated and the biosolubility is reduced.

[0051] By setting the lower limit of the above formula (1) or the above formula (2) to 20.8 or more, and preferably to 27.0 or more, there is a tendency that the glass filaments are not easily degraded when absorbing water while maintaining the biosolubility of the glass filaments. In addition, by setting the upper limit of the above formula (1) or the above formula (2) to 34.0 or less, and preferably to 33.0 or less, the biosolubility is improved, and the stability of the long fiberization is improved by increasing the operating temperature range.

[0052] The content of each component in the glass composition for glass fiber of the present embodiment can be measured by using an ICP emission spectrometer to measure the oil content of Li as a light element, and by using a wavelength dispersive X-ray fluorescence analyzer to measure the content of other elements. Specifically, the content of each component can be measured in the following manner.

[0053] First, a glass batch or glass fiber mixed with glass raw materials is placed in a platinum crucible, and in an electric furnace, it is kept at a temperature of 1350-1550°C for 6 hours when a glass batch is used; when glass fiber is used, it is kept at a temperature of 1300-1450°C for 6 hours, and is stirred while melting, thereby obtaining a homogeneous molten glass. Among them, in the case where organic matter is attached to the surface of the glass fiber or in the case where an organic matter such as a resin mainly contains glass fiber as a reinforcing material, the glass fiber is used after removing the organic matter by heating in a muffle furnace at 300-650°C for about 0.5-24 hours.

[0054] Next, the obtained molten glass is poured onto a carbon plate, and after making glass scraps, it is crushed to powderize it to make glass powder. After the above-mentioned glass powder is heated and decomposed with acid, an ICP emission spectrophotometer is used to perform a quantitative analysis on Li as a light element. After the above-mentioned glass powder can be formed into a disc shape using a pressing machine, a wavelength dispersive fluorescence X-ray analyzer is used to perform a quantitative analysis on other elements. The quantitative analysis using a wavelength dispersive fluorescence X-ray analyzer can be specifically carried out in the following manner: a sample for a standard curve is prepared based on the results measured by the fundamental parameter method, and the sample is analyzed by the standard curve method. It should be noted that the content of each component in the sample for the calibration curve can be quantitatively analyzed by an ICP emission spectrophotometer.

[0055] These quantitative analysis results are converted into oxides to calculate the content and total amount of each component, and the content rate (mass %) of each component mentioned above can be obtained based on these numerical values.

[0056] Next, the glass fiber of the present embodiment includes glass filaments formed of the glass composition for glass fibers of the present embodiment described above. The glass fiber of the present embodiment can be produced as follows.

[0057] First, glass raw materials (batch glass materials) prepared in a manner to become the composition of the glass composition for glass fiber of the present embodiment based on the components contained in the ore as glass raw materials, the content ratio of each component, and the volatilization amount of each component during the melting process are supplied to a melting furnace and melted at a temperature ranging from 1350 to 1550° C. Next, the melted batch glass material (molten glass) is pulled out from 1 to 20,000 nozzle heads of a sleeve controlled at a predetermined temperature and quenched to form glass filaments.

[0058] Next, a sizing agent or a binder is applied to the formed glass filaments using a coater as a coating device, and 1 to 20,000 glass filaments are bundled using a bundler and wound onto a bobbin at high speed using a winder, thereby obtaining glass fibers.

[0059] In order to manufacture the glass fiber of the glass composition for glass fiber of the present embodiment into the above-mentioned glass fiber, when the glass composition for glass fiber is melted at a temperature in the above-mentioned range, by using the operating temperature range ΔT calculated by the 1000 poise temperature and the liquidus temperature (operating temperature range ΔT = 1000 poise temperature - liquidus temperature) to be above 0°C, long fiberization can be achieved. By making the operating temperature range ΔT above 100°C, long fiberization can be easily achieved.

[0060] Among them, the glass single fiber (glass filament) ejected from a nozzle head or hole and cooled and solidified usually has a perfect circular cross-sectional shape, and preferably has a diameter (filament diameter) less than 3.0 μm. On the other hand, in the case where the above-mentioned nozzle head has a non-circular shape and has a protrusion or a cutout for quenching the molten glass, by controlling the temperature conditions, it is possible to obtain glass filaments with non-circular cross-sectional shapes such as elliptical and oblong. In the case where the glass filament has an elliptical or oblong cross-sectional shape, the fiber diameter when the cross-sectional area is converted into a perfect circle, that is, the converted fiber diameter is preferably less than 3.0 μm. It should be noted that the lower limit of the above-mentioned filament diameter is, for example, 0.5 μm, preferably 1.0 μm, and more preferably 2.0 μm.

[0061] The filament diameter of the above-mentioned glass filaments can be calculated, for example, in the following manner. First, glass fiber is embedded in a resin such as epoxy resin and the resin is cured, the cured resin is cut and its cross section is ground. Then, an electron microscope is used to observe the cross section of the cured resin, and for more than 50 glass filaments exposed from the above-mentioned cross section, when the cross-sectional shape of the glass filament is a perfect circle or a roughly perfect circle, the diameter of the glass filament is measured. In addition, when the cross-sectional shape of the glass filament is other than a perfect circle or a roughly perfect circle, its cross-sectional area is calculated, and then the converted fiber diameter is calculated based on the cross-sectional area. Then, the average value of the measured or calculated diameter or the converted fiber diameter is obtained, and the filament diameter of the glass filament is calculated. In addition, the filament diameter of the above-mentioned glass filament can also be measured by performing image processing on the image obtained by the electron microscope using an automatic analysis device.

[0062] On the other hand, when the glass fiber of the present embodiment is included in the glass fiber reinforced resin molded product, the filament diameter of the glass filament can be measured, for example, in the following manner. First, the glass fiber reinforced resin molded product is heated at a temperature of 625° C. for 30 minutes, and the thermoplastic resin is burned to remove the glass fiber. Then, the filament diameter of the glass filament is measured in the same manner as the above-mentioned method for measuring the filament diameter of the glass filament in the glass fiber.

[0063] In order to improve the bundling of glass filaments, improve the adhesion of glass fiber to resin, improve the uniform dispersion of glass fiber in a mixture of glass fiber and resin or inorganic material, etc., the glass fiber of the present embodiment can be coated with an organic substance. As such an organic substance, starch, polyurethane resin, epoxy resin, vinyl acetate resin, acrylic resin, modified polypropylene, especially carboxylic acid-modified polypropylene, (poly) carboxylic acid, especially copolymers of maleic acid and unsaturated monomers, etc. can be cited.

[0064] In addition, the glass fiber of the present embodiment can be coated with a resin composition containing a silane coupling agent, a lubricant, a surfactant, etc. in addition to the above-mentioned resin coating. In addition, the glass fiber of the present embodiment can also be coated with a treatment agent composition that does not contain the above-mentioned resin but contains a silane coupling agent, a surfactant, etc. Based on the mass of the glass fiber of the present embodiment in a state not coated with the resin composition or the treatment agent composition, the resin composition or the treatment agent composition coats the glass fiber at a ratio of 0.03 to 2.0 mass%.

[0065] It should be noted that the coating of the glass fiber with the organic substance can be carried out, for example, by the following method: in the manufacturing process of the glass fiber, a known method such as a roller coater is used to apply a resin solution or a resin composition solution to the glass fiber, and then the glass fiber coated with the resin solution or the resin composition solution is dried. In addition, the coating of the glass fiber with the above-mentioned organic substance can also be carried out in the following manner: the glass fiber of the present embodiment in the form of a fabric is immersed in a treatment agent composition solution, and then the glass fiber coated with the treatment agent composition is dried.

[0066] Among them, examples of silane coupling agents include aminosilane, ureidosilane, chlorosilane, epoxysilane, mercaptosilane, vinylsilane, (meth)acrylic silane, phenylsilane, styrylsilane, and isocyanate silane. In this embodiment, each of the above silane coupling agents may be used alone or in combination of two or more.

[0067] Examples of the aminosilane include γ-aminopropyltriethoxysilane, N-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, N-β-(aminoethyl)-N′-β-(aminoethyl)-γ-aminopropyltrimethoxysilane, and γ-anilinopropyltrimethoxysilane.

[0068] Examples of the ureidosilane include γ-ureidopropyltriethoxysilane and the like.

[0069] Examples of the chlorosilane include γ-chloropropyltrimethoxysilane and the like.

[0070] Examples of epoxysilane include β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane and γ-glycidoxypropyltrimethoxysilane.

[0071] Examples of the mercaptosilane include γ-mercaptotrimethoxysilane and γ-mercaptopropyltrimethoxysilane.

[0072] Examples of the vinyl silane include vinyltrimethoxysilane, N-β-(N-vinylbenzylaminoethyl)-γ-aminopropyltrimethoxysilane, and N-benzyl-β-aminoethyl-γ-aminopropyltrimethoxysilane.

[0073] Examples of the (meth)acrylic silane include γ-acryloxypropyltrimethoxysilane and γ-methacryloxypropyltrimethoxysilane.

[0074] Examples of the phenylsilane include phenyltrimethoxysilane and the like.

[0075] Examples of the styrylsilane include p-styryltrimethoxysilane.

[0076] Examples of the isocyanate silane include γ-isocyanate propyltriethoxysilane and the like.

[0077] As lubricants, there can be mentioned: modified silicone oil, animal oil and hydrogenated additives thereof, vegetable oil and hydrogenated additives thereof, animal wax, vegetable wax, mineral wax, condensation products of higher saturated fatty acids and higher saturated alcohols, polyethylene imine, polyalkyl polyamine alkyl linolenic acid derivatives, fatty acid amides, quaternary ammonium salts. In the present embodiment, the above lubricants can be used alone or in combination of two or more.

[0078] Examples of animal oils include beef tallow and the like.

[0079] Examples of the vegetable oil include soybean oil, coconut oil, rapeseed oil, palm oil, and castor oil.

[0080] Examples of the animal wax include beeswax and lanolin.

[0081] Examples of the vegetable wax include candelilla wax and carnauba wax.

[0082] Examples of the mineral wax include paraffin wax and montan wax.

[0083] Examples of the condensate of a higher saturated fatty acid and a higher saturated alcohol include stearic acid esters such as lauryl stearic acid.

[0084] Examples of the fatty acid amide include dehydration condensates of polyethylene polyamines such as diethylenetriamine, triethylenetetramine, and tetraethylenepentamine, and fatty acids such as lauric acid, myristic acid, palmitic acid, and stearic acid.

[0085] Examples of the quaternary ammonium salt include alkyltrimethylammonium salts such as lauryltrimethylammonium chloride.

[0086] Examples of the surfactant include nonionic surfactants, cationic surfactants, anionic surfactants, and amphoteric surfactants. In the present embodiment, each of the above surfactants may be used alone or in combination of two or more.

[0087] Examples of the nonionic surfactant include ethylene oxide propylene oxide alkyl ethers, polyoxyethylene alkyl ethers, polyoxyethylene-polyoxypropylene-block copolymers, alkyl polyoxyethylene-polyoxypropylene-block copolymer ethers, polyoxyethylene fatty acid esters, polyoxyethylene fatty acid monoesters, polyoxyethylene fatty acid diesters, polyoxyethylene sorbitan fatty acid esters, glycerol fatty acid ester ethylene oxide adducts, ethylene oxide propylene oxide alkyl ethers, hydrogenated castor oil ethylene oxide adducts, alkylamine ethylene oxide adducts, fatty acid amide ethylene oxide adducts, glycerol fatty acid esters, polyglycerol fatty acid esters, pentaerythritol fatty acid esters, sorbitol fatty acid esters, sorbitol fatty acid esters, sucrose fatty acid esters, polyhydric alcohol alkyl ethers, fatty acid alkanolamides, acetylene glycols, ethylene oxide adducts of acetylene glycols, and ethylene oxide adducts of acetylene alcohols.

[0088] Examples of the cationic surfactant include alkyldimethylbenzylammonium chloride, alkyltrimethylammonium chloride, alkyldimethylethylammonium ethylsulfate, higher alkylamine salts (acetates, hydrochlorides, etc.), ethylene oxide adducts of higher alkylamines, condensates of higher fatty acids and polyalkylenepolyamines, salts of esters of higher fatty acids and alkanolamines, salts of higher fatty acid amides, imidazoline-type cationic surfactants, and alkylpyridinium salts.

[0089] Examples of the anionic surfactant include higher alcohol sulfates, higher alkyl ether sulfates, α-olefin sulfates, alkylbenzene sulfonates, α-olefin sulfonates, reaction products of fatty acid halides and N-methyltaurine, dialkyl sulfosuccinates, higher alcohol phosphates, and phosphates of higher alcohol ethylene oxide adducts.

[0090] Examples of the amphoteric surfactant include amino acid-type amphoteric surfactants such as alkylaminopropionic acid alkali metal salts, betaine-type amphoteric surfactants such as alkyldimethylbetaine, and imidazoline-type amphoteric surfactants.

[0091] Examples of the form of glass fiber include woven fabric (glass cloth), knitted fabric, yarn, chopped strands, roving, chopped strand mat, fiber paper, fiber web, woven cloth, milled fiber, etc., with chopped strands, roving, and woven fabric (glass cloth) being preferred, and woven fabric (glass cloth) being more preferred.

[0092] For example, when the glass fiber of the present embodiment is chopped strands, the number of glass filaments constituting the glass fiber of the present embodiment is, for example, 10 to 20,000, preferably 50 to 10,000, and more preferably 1,000 to 8,000. In addition, the length of the chopped strands of the glass fiber of the present embodiment can be, for example, 1.0 to 100.0 mm, preferably 1.2 to 51.0 mm, more preferably 1.5 to 30.0 mm, further preferably 2.0 to 15.0 mm, and particularly preferably 2.3 to 7.8 mm. Here, the chopped strands can be obtained by cutting the glass fiber prepared by the above method into a prescribed length by a known device such as a long fiber cutting device. Among them, the long fiber cutting device is a device for cutting the glass strands fed between a cutter roll and a rubber roll, on which cutters (cutting blades) are installed at equal intervals and radially, and the rubber roll rotates in contact with the cutter roll and is equipped with rubber on the outer peripheral surface.

[0093] When the glass fiber of the present embodiment is a roving, the number of glass filaments constituting the glass fiber of the present embodiment is, for example, 200 to 30000. The roving as the glass fiber of the present embodiment has a mass per unit length of 0.5 to 10000 tex (g / 1000 m).

[0094] The glass fiber fabric of the present embodiment is composed of the above-mentioned glass fiber of the present embodiment. The glass fabric of the present embodiment can be obtained by weaving the above-mentioned glass fiber of the present embodiment as warp and weft using a loom known to itself. As the above-mentioned loom, for example, jet looms such as air jet looms or water jet looms, shuttle looms, rapier looms, etc. can be cited. In addition, as the weaving method using the above-mentioned loom, for example, plain weave, satin weave, square weave, twill weave, etc. can be cited, and from the viewpoint of manufacturing efficiency, plain weave is preferred.

[0095] The above-mentioned glass fibers of this embodiment contained in the glass fiber fabric of this embodiment are composed of glass filaments having a filament diameter of 2.0 μm or more and 9.0 μm or less, and preferably have a mass of 0.35 to 70.0 tex (g / 1000 m), more preferably have a mass of 0.5 to 70.0 tex (g / 1000 m), further preferably consist of glass filaments having a filament diameter of 2.0 μm or more and less than 3.0 μm, further preferably have a mass of 0.35 to 1.5 tex, and particularly preferably have a mass of 0.5 to 1.5 tex.

[0096] Among them, the filament diameter of the glass fiber of this embodiment contained in the glass fiber fabric of this embodiment is the average value of the following measured values: the measured value when the diameter of at least 50 glass filaments constituting the glass fiber in the cross section of the above-mentioned glass fiber is measured using a scanning electron microscope (manufactured by JEOL Ltd., trade name: JSM-IT800, magnification: 3000 times).

[0097] In addition, the glass fiber woven fabric of the present embodiment is preferably composed of warp yarns having a weaving density of 40 to 150 yarns / 25 mm and weft yarns having a weaving density of 40 to 150 yarns / 25 mm.

[0098] In addition, the weaving density of the warp yarn can be obtained by counting the number of warp yarns within a range of 25 mm in the warp direction using a fabric analyzer according to JIS R 3420. In addition, the weaving density of the weft yarn can be obtained by counting the number of weft yarns within a range of 25 mm in the weft direction using a fabric analyzer according to JIS R 3420.

[0099] The glass fiber fabric of this embodiment may be subjected to deoiling treatment, surface treatment and fiber opening treatment after weaving.

[0100] The deoiling treatment includes a treatment in which the glass fiber fabric is placed in a heating furnace at an atmosphere temperature of 350° C. to 400° C. for 40 to 80 hours to heat and decompose organic matter adhering to the glass fiber.

[0101] As the surface treatment, the following treatment can be cited: immersing the glass fiber fabric in a solution containing the above-mentioned silane coupling agent or the above-mentioned silane coupling agent and the above-mentioned surfactant, squeezing out excess water, and then heating and drying at a temperature range of 80° C. to 180° C. for 1 to 30 minutes.

[0102] As the fiber opening treatment, for example, the following treatments can be cited: while applying a tension of 20 to 200N to the warp yarns of the glass fiber fabric, fiber opening using water flow pressure, fiber opening using high-frequency vibration using a liquid as a medium, fiber opening using pressure of a fluid having surface pressure, fiber opening using roller pressure, etc., to increase the width of the warp yarns and the weft yarns.

[0103] In addition, the glass fiber fabric of the present embodiment preferably has a weight of 2.5 to 220 g / m 2 The mass range is preferably 5.0 to 220 g / m 2 In addition, it is preferred that the thickness range is 4.0 to 200.0 μm.

[0104] In addition, the glass fiber fabric of the present embodiment may include a surface treatment layer containing the above-mentioned silane coupling agent or a surface treatment layer containing the above-mentioned silane coupling agent and the above-mentioned surfactant. When the glass fiber fabric of the present embodiment includes the surface treatment layer, the surface treatment layer may have a mass range of, for example, 0.03 to 1.50 mass % relative to the total amount of the glass fiber fabric including the surface treatment layer.

[0105] The glass fiber reinforced resin composition of the present embodiment contains the glass fiber of the present embodiment described above. Specifically, the glass fiber reinforced resin composition of the present embodiment is a glass fiber reinforced resin composition containing a resin (thermoplastic resin or thermosetting resin), glass fiber and other additives, wherein the glass fiber reinforced resin composition contains 10 to 90% by mass of glass fiber relative to the total amount of the glass fiber reinforced resin composition. In addition, the glass fiber reinforced resin composition of the present embodiment contains 90 to 10% by mass of resin relative to the total amount of the glass fiber reinforced resin composition, and contains other additives in the range of 0 to 40% by mass.

[0106] Among them, examples of the thermoplastic resin include polyethylene, polypropylene, polystyrene, styrene / maleic anhydride resin, styrene / maleimide resin, polyacrylonitrile, acrylonitrile / styrene (AS) resin, acrylonitrile / butadiene / styrene (ABS) resin, chlorinated polyethylene / acrylonitrile / styrene (ACS) resin, acrylonitrile / ethylene / styrene (AES) resin, acrylonitrile / styrene / methyl acrylate (ASA) resin, styrene / acrylonitrile (SAN) resin, methacrylic resin, polyvinyl chloride (PVC), polyvinylidene chloride (PVDC), polyamide, polyacetal, polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polytrimethylene terephthalate (PTT), polycarbonate, polyarylene sulfide, polyether sulfone (PES), polyphenylene sulfone (PPS U), polyphenylene ether (PPE), modified polyphenylene ether (m-PPE), polyaryletherketone, liquid crystal polymer (LCP), fluororesin, polyetherimide (PEI), polyarylate (PAR), polysulfone (PSF), polyamideimide (PAI), polyaminobismaleimide (PABM), thermoplastic polyimide (TPI), polyethylene naphthalate (PEN), ethylene / vinyl acetate (EVA) resin, ionomer (IO) resin, polybutadiene, styrene / butadiene resin, polybutene, polymethylpentene, olefin / vinyl alcohol resin, cyclic olefin resin, cellulose resin, polylactic acid, polyvinyl alcohol (PVA), polyglycolic acid (PGA), polybutylene succinate (PBS), polybutylene succinate adipate (PBSA), polybutylene adipate terephthalate (PBAT), etc.

[0107] Specifically, examples of polyethylene include high-density polyethylene (HDPE), medium-density polyethylene, low-density polyethylene (LDPE), linear low-density polyethylene (LLDPE), and ultra-high molecular weight polyethylene.

[0108] Examples of the polypropylene include isotactic polypropylene, atactic polypropylene, syndiotactic polypropylene, and mixtures thereof.

[0109] Examples of the polystyrene include general-purpose polystyrene (GPPS) which is atactic polystyrene having an atactic structure, high impact polystyrene (HIPS) obtained by adding a rubber component to GPPS, and syndiotactic polystyrene having an isotactic structure.

[0110] Examples of the methacrylic resin include polymers obtained by polymerizing one methacrylic acid resin selected from acrylic acid, methacrylic acid, styrene, methyl acrylate, ethyl acrylate, ethyl methacrylate, butyl acrylate, butyl methacrylate, and fatty acid vinyl esters alone, or polymers obtained by copolymerizing two or more of the above methacrylic resins.

[0111] Examples of polyvinyl chloride include homopolymers of vinyl chloride polymerized by conventionally known methods such as emulsion polymerization, suspension polymerization, microsuspension polymerization, and bulk polymerization, copolymers with monomers copolymerizable with vinyl chloride monomers, and graft copolymers in which vinyl chloride monomers are graft-polymerized onto polymers.

[0112] Examples of polyamides include polycaprolactam (nylon 6), polyhexamethylene adipamide (nylon 66), polybutylene adipamide (nylon 46), polybutylene sebacate (nylon 410), polypentamethylene adipamide (nylon 56), polysebamide (nylon 510), polyhexamethylene sebacate (nylon 610), polyhexamethylene dodecanoamide (nylon 612), polydecamethylene adipamide (nylon 106), polydecanediamide (nylon 410), polypentamethylene adipamide (nylon 56), polysebamide (nylon 510), polyhexamethylene sebacate (nylon 610), polydodecanediamide (nylon 612), polydecamethylene adipamide (nylon 106), polydecanediamide (nylon 410). (Nylon 1010), polydodecane diamide (Nylon 1012), polyundecanamide (Nylon 11), polyhexamethylene adipamide (Nylon 116), polydodecane amide (Nylon 12), polyxylene hexamethylenediamine (Nylon XD6), polyxylene sebacic acid amide (Nylon XD10), polymethylene adipamide (Nylon MXD6), polymethylene adipamide (Nylon PXD6), polyterephthalamide (Nylon 4T), poly Pentamethylene terephthalamide (nylon 5T), polyhexamethylene terephthalamide (nylon 6T), polyhexamethylene isophthalamide (nylon 6I), polynonane terephthalamide (nylon 9T), polydecane terephthalamide (nylon 10T), polyundemethylene terephthalamide (nylon 11T), polydodecamethylene terephthalamide (nylon 12T), polytetramethylene phthalamide (nylon 4I), polybis(3-methyl-4-aminohexamethylene terephthalamide) One of the components selected from the group consisting of poly(3-methyl-4-aminohexyl)methane terephthalamide (nylon PACMT), poly(3-methyl-4-aminohexyl)methane isophthalamide (nylon PACMI), poly(3-methyl-4-aminohexyl)methane dodecanamide (nylon PACM12), poly(3-methyl-4-aminohexyl)methane tetradecanoamide (nylon PACM14), or a copolymer of two or more of the components, or a mixture of these components.

[0113] Examples of the polyacetal include homopolymers having oxymethylene units as main repeating units and copolymers of oxyalkylene units mainly containing oxymethylene units, and copolymers of oxyalkylene units having 2 to 8 adjacent carbon atoms in the main chain of the oxyalkylene units.

[0114] Examples of polyethylene terephthalate include polymers obtainable by polycondensation of terephthalic acid or a derivative thereof with ethylene glycol.

[0115] Examples of the polybutylene terephthalate include polymers obtainable by polycondensing terephthalic acid or a derivative thereof with 1,4-butanediol.

[0116] Examples of the polytrimethylene terephthalate include polymers obtainable by polycondensing terephthalic acid or a derivative thereof with 1,3-propylene glycol, and the like.

[0117] Examples of the polycarbonate include polymers obtained by an ester exchange method in which a dihydroxydiaryl compound is reacted with a carbonate such as diphenyl carbonate in a molten state, and polymers obtained by a phosgene method in which a dihydroxydiaryl compound is reacted with phosgene.

[0118] Examples of the polyarylene sulfide include linear polyphenylene sulfide, cross-linked polyphenylene sulfide that has a high molecular weight by a curing reaction after polymerization, polyphenylene sulfide sulfone, polyphenylene sulfide ether, and polyphenylene sulfide ketone.

[0119] Examples of the polyphenylene ether include poly(2,3-dimethyl-6-ethyl-1,4-phenylene ether), poly(2-methyl-6-chloromethyl-1,4-phenylene ether), poly(2-methyl-6-hydroxyethyl-1,4-phenylene ether), poly(2-methyl-6-n-butyl-1,4-phenylene ether), poly(2-ethyl-6-isopropyl-1,4-phenylene ether), poly(2-ethyl-6-n-propyl-1,4-phenylene ether), poly(2,3,6-trimethyl-1,4-phenylene ether), poly[2-(4'-methylphenyl)-1,4-phenylene ether], poly(2-bromo-6-phenyl-1,4-phenylene ether), poly(2-methyl-6-phenyl-1,4-phenylene ether), poly(2-phenyl-1 ,4-phenylene ether), poly(2-chloro-1,4-phenylene ether), poly(2-methyl-1,4-phenylene ether), poly(2-chloro-6-ethyl-1,4-phenylene ether), poly(2-chloro-6-bromo-1,4-phenylene ether), poly(2,6-di-n-propyl-1,4-phenylene ether), poly(2-methyl-6-isopropyl-1,4-phenylene ether), poly(2-chloro-6-methyl-1,4-phenylene ether), poly(2-methyl-6-ethyl-1,4-phenylene ether), poly(2,6-dibromo-1,4-phenylene ether), poly(2,6-dichloro-1,4-phenylene ether), poly(2,6-diethyl-1,4-phenylene ether), poly(2,6-dimethyl-1,4-phenylene ether), and the like.

[0120] Examples of the modified polyphenylene ether include polymer alloys of poly(2,6-dimethyl-1,4-phenylene) ether and polystyrene, polymer alloys of poly(2,6-dimethyl-1,4-phenylene) ether and styrene / butadiene copolymers, polymer alloys of poly(2,6-dimethyl-1,4-phenylene) ether and styrene / maleic anhydride copolymers, polymer alloys of poly(2,6-dimethyl-1,4-phenylene) ether and polyamides, polymer alloys of poly(2,6-dimethyl-1,4-phenylene) ether and styrene / butadiene / acrylonitrile copolymers, modified polyphenylene ethers having functional groups such as amino groups, epoxy groups, carboxyl groups, styryl groups introduced into polymer chain terminals of the above polyphenylene ethers, and modified polyphenylene ethers having functional groups such as amino groups, epoxy groups, carboxyl groups, styryl groups, methacryl groups introduced into polymer chain side chains of the above polyphenylene ethers.

[0121] Examples of the polyaryletherketone include polyetherketone (PEK), polyetheretherketone (PEEK), polyetherketoneketone (PEKK), and polyetheretherketoneketone (PEEKK).

[0122] As liquid crystal polymers (LCP), there can be mentioned (co)polymers composed of structural units of one or more components selected from the following components, namely: aromatic hydroxycarbonyl units, aromatic dihydroxy units, aromatic dicarbonyl units, aliphatic dihydroxy units, aliphatic dicarbonyl units, etc. as thermotropic liquid crystal polyesters.

[0123] Examples of the fluororesin include polytetrafluoroethylene (PTFE), perfluoroalkoxy resin (PFA), fluorinated ethylene propylene resin (FEP), fluorinated ethylene tetrafluoroethylene resin (ETFE), polyethylene fluoride (PVF), polyvinylidene fluoride (PVDF), polychlorotrifluoroethylene (PCTFE), and ethylene / chlorotrifluoroethylene resin (ECTFE).

[0124] Examples of the ionomer (IO) resin include copolymers of olefins or styrene and unsaturated carboxylic acids, wherein a part of the carboxyl groups are neutralized with metal ions.

[0125] Examples of the olefin / vinyl alcohol resin include ethylene / vinyl alcohol copolymers, propylene / vinyl alcohol copolymers, ethylene / vinyl acetate copolymer saponification products, and propylene / vinyl acetate copolymer saponification products.

[0126] Examples of the cyclic olefin resin include monocyclic compounds such as cyclohexene, polycyclic compounds such as tetracyclic cycloolefins, and polymers of cyclic olefin monomers.

[0127] Examples of the polylactic acid include poly-L-lactic acid which is an L-form homopolymer, poly-D-lactic acid which is a D-form homopolymer, and stereocomplex polylactic acid which is a mixture thereof.

[0128] Examples of the cellulose resin include methyl cellulose, ethyl cellulose, hydroxy cellulose, hydroxymethyl cellulose, hydroxyethyl cellulose, hydroxyethyl methyl cellulose, hydroxypropyl methyl cellulose, cellulose acetate, cellulose propionate, and cellulose butyrate.

[0129] In addition, examples of the aforementioned thermosetting resins include: unsaturated polyester resins, vinyl ester resins, epoxy (EP) resins, melamine (MF) resins, phenolic resins (PF), polyurethane resins (PU), polyisocyanates, polyisocyanurates, modified polyimide (PI) resins, urea-formaldehyde (UF) resins, silicone (SI) resins, furan (FR) resins, benzoguanamine (BR) resins, alkyd resins, xylene resins, bismaleimide triazine (BT) resins, diallyl phthalate resins (PDAP), and the like.

[0130] Specifically, examples of the unsaturated polyester resin include resins obtained by esterification reaction of an aliphatic unsaturated dicarboxylic acid and an aliphatic diol.

[0131] Examples of the vinyl ester resin include divinyl ester resins and novolac-based vinyl ester resins.

[0132] Examples of the epoxy resin include bisphenol A epoxy resin, bisphenol F epoxy resin, bisphenol E epoxy resin, bisphenol S epoxy resin, bisphenol M epoxy resin (4,4'-(1,3-phenylene diisopropylidene) bisphenol type epoxy resin), bisphenol P epoxy resin (4,4'-(1,4-phenylene diisopropylidene) bisphenol type epoxy resin), bisphenol Z epoxy resin (4,4'-cyclohexylene diphenol type epoxy resin), phenol novolac epoxy resin, cresol novolac epoxy resin, and tetraphenylethane novolac epoxy resin. Varnish type epoxy resin, novolac type epoxy resin having a condensed aromatic hydrocarbon structure, biphenyl type epoxy resin, xylene type epoxy resin or phenyl aralkyl type epoxy resin and other aralkyl type epoxy resins, naphthylene ether type epoxy resin, naphthol type epoxy resin, naphthalene diol type epoxy resin, bifunctional or tetrafunctional epoxy type naphthalene resin, binaphthyl type epoxy resin, naphthalene aralkyl type epoxy resin, anthracene type epoxy resin, phenoxy type epoxy resin, dicyclopentadiene type epoxy resin, norbornene type epoxy resin, adamantane type epoxy resin, fluorene type epoxy resin, etc.

[0133] Examples of the melamine resin include polymers formed by polycondensation of melamine (2,4,6-triamino-1,3,5-triazine) and formaldehyde.

[0134] Examples of the phenolic resin include novolac-type phenolic resins such as phenol novolac resins, cresol novolac resins, and bisphenol A novolac resins, resol-type phenolic resins such as methylol resol resins and dimethylene ether resol resins, and aryl alkylene phenolic resins, or a combination of two or more of these resins.

[0135] Examples of the urea-formaldehyde resin include resins obtained by condensation of urea and formaldehyde.

[0136] The above-mentioned thermoplastic resin or the above-mentioned thermosetting resin may be used alone or in combination of two or more kinds.

[0137] Examples of the other additives include reinforcing fibers other than glass fibers such as carbon fibers and metal fibers, fillers other than glass fibers such as glass powder, talc, and mica, flame retardants, ultraviolet absorbers, heat stabilizers, antioxidants, antistatic agents, flow improvers, antiblocking agents, lubricants, nucleating agents, antibacterial agents, pigments, and the like.

[0138] The glass fiber reinforced resin composition of the present embodiment may be a prepreg obtained by impregnating the glass fiber woven fabric of the present embodiment with the resin by a known method and semi-curing the impregnated glass fiber woven fabric.

[0139] The glass fiber reinforced resin composition of the present embodiment can be molded by known molding methods to obtain various glass fiber reinforced resin molded products. As known molding methods, injection molding, injection compression molding, two-color molding, hollow molding, foaming molding including supercritical fluid, insert molding, in-mold coating molding, autoclave molding, extrusion molding, sheet molding, thermoforming, rotational molding, stacking molding, compression molding, blow molding, stamping molding, infusion molding, hand paste molding, spraying, RIM low-pressure molding, resin transfer molding, sheet molding compound molding, mass molding compound molding, pultrusion molding, filament winding, etc. In addition, by curing the above-mentioned prepreg, glass fiber reinforced resin molded products can also be obtained.

[0140] Examples of uses of such molded articles include printed wiring boards, electronic parts such as connectors, housings of electronic devices, vehicle interior parts, vehicle exterior parts, housings of electronic devices such as antennas and radars, and separators of fuel cells.

[0141] Next, examples of the present invention and comparative examples are shown.

[0142] Example

[0143] [Examples 1 to 4, Comparative Examples 1 to 4, Reference Example]

[0144] First, glass raw materials were mixed to prepare glass batches so that the glass compositions after melting and solidification would be the compositions of Examples 1 to 4, Comparative Examples 1 to 4, and Reference Example shown in Table 2.

[0145] Next, the obtained glass batch material was placed in a platinum crucible, and the platinum crucible was kept in an electric furnace for 4 hours under a temperature range of 1350 to 1550° C., which is a melting temperature suitable for the glass batch materials of each embodiment, comparative example and reference example, while stirring the glass batch material to melt, thereby obtaining a homogeneous molten glass. Next, the obtained molten glass was poured onto a carbon plate and cooled to obtain block-shaped glass scraps.

[0146] Next, the obtained glass chips were used to evaluate biosolubility, long fiber formation possibility, and strength when absorbing water by the following methods.

[0147] It should be noted that the total elution rate of Si, B, Al and Ca of the glass fiber obtained from the glass composition for glass fiber of Example 1 was 106 μg / h, the operating temperature range was 159° C., and the linear expansion coefficient was 5.5 ppm / K.

[0148] 〔Biological solubility〕

[0149] First, the aforementioned glass scraps are put into a platinum container having a nozzle head at the bottom, and the platinum container is heated to a temperature range of 1150 to 1350°C to melt the glass scraps to obtain molten glass. Next, the molten glass is pulled out from the nozzle head and wound up on a winding device. Next, the heating temperature of the platinum container and the winding speed of the winding device are adjusted, and the glass fiber is wound on the winding device at a heating temperature of 1150 to 1350°C suitable for the glass composition of each embodiment, comparative example and reference example and a winding speed of 600 to 1200 rpm suitable for the glass composition of each embodiment, comparative example and reference example to obtain a glass fiber sample with a filament diameter of 13.0 μm.

[0150] Next, the dissolution test of the glass fiber sample was conducted according to K. Sebastian. et al., Glass Science and Technology, Vol. 75, pp. 263-270 (2002). Specifically, first, the reagents No. 1 to 12 shown in Table 1 were added in sequence to about 800 mL of distilled water kept at 37°C, and the pH was adjusted to 4.5 using hydrochloric acid No. 13, and finally adjusted to 1 L, to prepare an artificial lung fluid with a pH of 4.5 that simulates the intrapulmonary environment and has the composition shown in Table 1. Next, the prepared artificial lung fluid was allowed to stand for 24 hours. Next, the pH of the artificial lung fluid after standing still increased with the release of carbon dioxide, so the pH of the artificial lung fluid kept at 37°C was adjusted to 4.5 again using hydrochloric acid.

[0151] It is known that fibers are taken up by macrophages after being inhaled into the lungs, and the pH around macrophages is 4.5. Therefore, it is expected that fibers having high solubility in artificial lung fluid having a pH of 4.5 will be dissolved in the lungs.

[0152] [Table 1]

[0153] No. Composition of artificial lung fluid Content (g / L) 1 Sodium chloride 7.12 2 Sodium bicarbonate 1.95 3 Calcium chloride 0.022 4 Disodium hydrogen phosphate 0.148 5 Sodium sulfate 0.079 6 Magnesium chloride hexahydrate 0.212 7 Glycine 0.118 8 Trisodium citrate dihydrate 0.152 9 Sodium tartrate dihydrate 0.18 10 Sodium pyruvate 0.172 11 90% lactic acid 0.156 12 formaldehyde 3mL 13 Hydrochloric acid (1:1) 4-5mL

[0154] Next, the above-mentioned glass fiber sample is cut into a length that can be accommodated in an in-line filter holder, that is, a length of 1 to 3 mm, to prepare a glass fiber sample for dissolution test. The above-mentioned glass fiber sample for dissolution test is placed on a membrane filter with a pore size of 0.2 μm set in the in-line filter holder, and the above-mentioned artificial lung fluid heated to 37°C is transported by a pump at a flow rate of 140 to 170 mL / day and sent into the in-line filter holder, and the filtrate that has passed through the test glass fiber sample and the filter holder is accumulated in a container, thereby implementing the dissolution test. At this time, the flow rate of the artificial lung fluid (unit: μm 3 / s) and sample surface area (unit: μm 2 The mass of the sample placed on the membrane filter was adjusted so that the ratio (flow rate of artificial lung fluid / surface area of ​​sample) became 0.030±0.005 μm / s.

[0155] After 24 hours, the filtrate was recovered from the container, and Si, Al, B, and Ca were used as the analyte ions, and the dissolved ion components in the filtrate were quantitatively analyzed using inductively coupled plasma emission spectrometry (IPC-AES). The quantitative results (μg) of ICP30-AES for Si, Al, B, and Ca were converted into oxides and divided by 24 hours to calculate the dissolution rate (μg / h) of each component. When the dissolution rate (μg / h) of each component is more than 100μg / h, the biosolubility is evaluated as "OK", and when the dissolution rate (μg / h) of each component is less than 100μg / h, the biosolubility is evaluated as "NG". The results are shown in Table 2.

[0156] 〔Possibility of long fibrosis〕

[0157] The glass scraps were melted in a platinum crucible using a high-temperature electric furnace equipped with a rotational viscometer (manufactured by Motoyama Co., Ltd.). The viscosity of the molten glass was continuously measured while the melting temperature was changed using the rotational viscometer. The temperature corresponding to a rotational viscosity of 1000 poise was measured, thereby determining the 1000 poise temperature.

[0158] Next, 40 g of glass particles with a particle size of 0.5 to 1.5 mm obtained by crushing the above glass scraps were placed in a 180×20×15 mm platinum vessel, and heated for more than 8 hours in a tubular electric furnace with a temperature gradient set at 900 to 1300° C., and then the vessel was taken out of the tubular electric furnace and observed with a polarizing microscope to determine the position where crystals of the devitrified glass began to precipitate. The temperature in the tubular electric furnace was measured using a B thermocouple, and the temperature at the position where precipitation began was obtained as the liquidus temperature.

[0159] Next, the operating temperature range ΔT (ΔT = 1000 poise temperature - liquidus temperature) was calculated based on the 1000 poise temperature and liquidus temperature measured by the above method. When ΔT was 100°C or higher, the possibility of long fiber formation was evaluated as "A", when ΔT was 0°C or higher and less than 100°C, the possibility of long fiber formation was evaluated as "B", and when ΔT was less than 0°C, the possibility of long fiber formation was evaluated as "C". The results are shown in Table 2.

[0160] 〔Strength when absorbing water〕

[0161] The glass scraps prepared are put into a platinum container having a nozzle head at the bottom, and the platinum container is heated to a temperature range of 1150°C to 1350°C to melt the glass scraps to obtain molten glass. Then, the molten glass is pulled out from the nozzle head and wound on a winding device. Next, the heating temperature of the platinum container and the winding speed of the winding device are adjusted, and the glass fiber is wound on the winding device at a heating temperature in the temperature range of 1150 to 1350°C suitable for the glass composition of each embodiment, comparative example and reference example, and a winding speed in the range of 600 to 1200 rpm suitable for the glass composition of each embodiment, comparative example and reference example, to obtain a glass fiber with a filament diameter of 13.0 μm.

[0162] Next, one fiber (monofilament) between the nozzle head and the winding device is extracted, and the fiber in a state where it is not deteriorated by contact or friction is used as a sample.

[0163] Next, the above-mentioned monofilament was bonded to a predetermined backing paper having a hole with a diameter of 25 mm in the center. Next, the backing paper was completely immersed in distilled water at 25°C. After being immersed for 3 hours, the backing paper was taken out from the distilled water, and after being left to stand for 1 hour in a dryer set at 50°C to dry it, a test piece was made. The test piece was set on the fixture of a tensile testing machine (manufactured by ORIENTEC Co., Ltd.), and after cutting off the end of the backing paper, a tensile test was carried out at a crosshead speed of 5 mm / min. The strength when water absorbed was calculated based on the maximum load value at break and the fiber cross-sectional area. The fiber cross-sectional area was calculated from the fiber diameter obtained by observing the monofilament using a scanning electron microscope (manufactured by JEOL Ltd., trade name: JSM-IT800). The test piece that was debonded during the measurement was excluded, and the average value of n=12 was taken as the measured value of the strength when water absorbed. The results are shown in Table 2.

[0164] 〔Linear expansion coefficient〕

[0165] In order to remove the strain of the above-mentioned glass scraps, the test piece was heated at a slow cooling temperature (550-750°C) for 2 hours and cooled to room temperature for 8 hours to obtain a test piece. Then, a cutting machine, such as a diamond cutter and a grinder, was used to process it into a 4mm×4mm×20mm linear expansion coefficient measurement test piece. Then, the obtained linear expansion coefficient measurement test piece was heated at a heating rate of 10°C / min, and the elongation was measured in a temperature range of 50-200°C using a thermal expansion coefficient measuring device (manufactured by NETZSCH, trade name: DIL402), and the linear expansion coefficient was calculated based on the elongation.

[0166] [Table 2]

[0167]

[0168] As is apparent from Table 2, the glass compositions for glass fibers of Examples 1 to 4 can provide glass filaments that have biosolubility, can be elongated, and have sufficiently high strength when absorbing water.

[0169] On the other hand, it is obvious that the glass filaments obtained from the glass fiber glass composition of Comparative Example 1 and Comparative Example 2, in which the ratio (MgO / CaO) of the content of MgO relative to the content of CaO is less than 0.29, have biosolubility, but cannot obtain sufficiently high strength when absorbing water. It is also known that the glass filaments obtained from the glass fiber glass composition of Comparative Example 3, in which the ratio (MgO / CaO) of the content of MgO relative to the content of CaO exceeds 1.92 and the total content of MgO and CaO is less than 17.09% by mass, have biosolubility, but cannot obtain sufficiently high strength when absorbing water, and the possibility of long fiberization is low. It is also obvious that the glass filaments obtained from the glass fiber glass composition of Comparative Example 4, in which the ratio (MgO / CaO) of the content of MgO relative to the content of CaO is within the scope of the present invention, but the total content of MgO and CaO is less than 17.09% by mass, have biosolubility, but cannot obtain sufficiently high strength when absorbing water.

[0170] Furthermore, the glass filaments made from the glass composition for glass fibers of the reference example in which the content of SiO2 relative to the total amount exceeds 50.00% by mass and the content of MgO is lower than 2.00% by mass are obviously not biosoluble. It should be noted that the glass composition of the glass composition for glass fibers of the reference example is the E glass composition which is the most common glass composition for glass fibers.

Claims

1. A glass composition for glass fiber, characterized in that: Relative to the total amount, including: 35.00 mass % to 50.00 mass % of SiO2, 12.00 mass% to 28.00 mass% of Al2O3, 10.00 mass% to 25.00 mass% of B2O3, 2.00 mass% to 18.00 mass% of MgO, 5.00 mass% to 25.00 mass% of CaO, The total content of MgO and CaO is in the range of 17.09 mass % to 30.00 mass %, The ratio of the content of MgO to the content of CaO, that is, MgO / CaO, is in the range of 0.29 to 1.

92.

2. The glass composition for glass fiber according to claim 1, characterized in that: The ratio of the content of MgO to the content of CaO, that is, MgO / CaO, is in the range of 0.49 to 1.

68.

3. A glass fiber, characterized in that: The invention comprises glass filaments formed from the glass composition for glass fibers according to claim 1.

4. The glass fiber according to claim 3, characterized in that The glass filaments have a filament diameter of less than 3.0 μm.

5. A glass fiber fabric, characterized in that: The glass fiber according to claim 3 or 4 is included.

6. A glass fiber reinforced resin composition, characterized in that: The glass fiber according to claim 3 or 4 is included.

Citation Information

Patent Citations

  • Glass composition for glass fiber, glass fiber, and sheet-shaped material of glass fiber

    CN102333735A

  • Composition for glass fiber, glass fiber, glass-fiber-containing composite material containing glass fiber, and method for manufacturing glass fiber

    CN110072824A

  • Glass fiber with high refractive index and high performance

    CN111233338A

  • Glass composition, glass fiber, glass cloth, and glass fiber production method

    CN113993825A

  • Glass fiber-reinforced resin composition and glass fiber-reinforced resin molded article

    CN114829504A